LITERATURE REVIEW : EFEKTIFITAS LATIHAN FIFA 11+ WARMUP TERHADAP LOWER LIMB INJURIES PADA PEMAIN FUTSALAMATIR - Muhamad Ariefin Saputra (2021)
Background: According to WHO (2018), it shows that the risk of futsal players being injured is a total of 1,000 games. Based on the information data that has been obtained related to the futsal sport that has been described, it shows that 108 futsal players have suffered minor injuries or injuries. Method: the literature review method used is by searching for journals on Google Scholar/, Bmc sports sciene medicine and rehabilitation asia pacific sport medicine, in the period 2021 - 2015. Five random control trail group journals were obtained. Results: in a study of 5 articles The journal produced an effective FIFA 11 WARM UP exercise for the precaution of lower limp injuries in futsal and amateur Fotball. Conclusion: from the search process for 5 articles in the FIFA 11+ WARM UP exercise journal, it is effective to prevent injuries to the lower limp body.